Detection of a novel panel of somatic mutations in plasma cell-free DNA and its diagnostic value in hepatocellular carcinoma - Xiong, Yu (Cancer Manag Res, 2019)
Background/aims: Circulating cell-free DNA (cfDNA) contains tumor-specific alterations and could potentially serve as “liquid biopsy”. The study was to identify a novel panel of hepatocellular carcinoma (HCC)-specific mutations in plasma cfDNA and to assess its value in the diagnosis of HCC. Materials and methods: 33 HCC tissue, 37 blood, and 37 swab specimens were collected from HCC patients and control individuals. Genomic DNA was subjected to next-generation sequencing. The selected mutations in the plasma cfDNA in the HCC versus control groups were compared, and the diagnostic performance of cfDNA mutations was evaluated. Results: A majority of selected mutations in the HCC tissue DNA, ranging from 52% to 84%, was detected in the matched plasma cfDNA. For the selected mutations, receiver operating characteristic (ROC) analysis revealed an area under the ROC curve (AUC) of 0.92, sensitivity of 65%, and specificity of 100% for the diagnosis of HCC regardless of alpha-fetoprotein (AFP) status. Detection of the selected mutations in cfDNA in combination with AFP exhibited better diagnosis performance, with AUC of 0.96, sensitivity of 73%, and specificity of 100% for AFP-negative patients, whereas the AUC was 0.86 with sensitivity of 53% and specificity of 100% for AFP-positive patients. Furthermore, the rates of the selected mutations were significantly greater in recurrent HCC than in non-recurrent HCC (P<0.05). Conclusions: This study has identified a novel panel of somatic mutations, and detection of the mutations in plasma cfDNA shows good diagnostic performance. Therefore, this approach holds promise as a novel tool for diagnosing HCC.